Emerging Role of Dipeptidyl Peptidase-4 in Autoimmune Disease - Huang, Jie; Liu, Xinxin; Wei, Yingying; Li, Xinlu; Gao, Shupei; Dong, Lingli; Rao, Xiaoquan; Zhong, Jixin (Frontiers in Immunology, 2022)
Dipeptidyl-peptidase IV (DPP4), originally identified as an aminopeptidase in 1960s, is a ubiquitously expressed protease presented either as a membrane-bound or soluble form. DPP4 cleaves dipeptide off from the N-terminal of its substrates, altering the bioactivity of its substrates. Subsequent studies reveal that DPP4 is also involved in various cellular processes by directly binding to a number of ligands, including adenosine deaminase, fibronectin, and caveolin-1. In recent years, many novel functions of DPP4, such as promoting fibrosis and mediating virus entry, have been discovered. Due to its implication in fibrotic response and immunoregulation, increasing studies are focusing on the potential role of DPP4 in inflammatory disorders. In this review, we will summarize the recent advances of DPP4 in immune regulation and autoimmune rheumatic disease.